2021
DOI: 10.1002/jctb.6817
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl ether conversion to light olefins in slurry and fixed‐bed reactors: coke nature and location on Mg/ZSM‐5 catalyst

Abstract: BACKGROUND The goal of this study was to investigate the deactivation of ZSM‐5 in the DTO process (dimethyl ether to light olefins) in a slurry reactor (SLR) in polydimethylsiloxane dispersion medium compared with its deactivation in a fixed‐bed reactor (FBR), and to unveil reasons behind the rapid deactivation of the catalyst in the SLR. RESULTS Under suspension conditions coke formation proceeds more slowly compared with fixed‐bed conditions: The amount of coke formed under suspension conditions is less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…These observations validate the presence of the inorganic-organic hybrid structure of D3. 48,49 Fig. 3(c) (XPS) shows the steady Si 2p peak of Si-O-Si at a binding energy of 105.5 eV, followed by 283.7 eV, indicating the C1s peak of C-Si (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These observations validate the presence of the inorganic-organic hybrid structure of D3. 48,49 Fig. 3(c) (XPS) shows the steady Si 2p peak of Si-O-Si at a binding energy of 105.5 eV, followed by 283.7 eV, indicating the C1s peak of C-Si (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, mass loss at temperatures from 200 to 500 • C is caused by the removal of amorphous carbon through the oxidation of CO to CO 2 , while fibrous and graphitic carbons undergo gasification at higher temperatures [75]. T. K. Obukhova et al [76] carried out tests in a tubular-bore reactor (FBR) and in a slurry suspension reactor (SLR) using the Mg/ZSM-5 catalyst. The TGA tests showed that, at a temperature of about 100 degrees, water desorption and the degassing of weakly bound hydrocarbon-derived impurities take place in the pores of the catalyst.…”
Section: (A) Thermogravimetric Analysis-tgamentioning
confidence: 99%
“…Another issue that needs to be addressed is the implementation of temperature control and cooling systems due to the exothermic nature of the DME synthesis reaction. Conducting the DME synthesis at temperatures above 300 • C leads to the deactivation of the metal catalyst through the deposition of coke on the walls of the reactor [76,[86][87][88].…”
Section: Conventional Reactors (A) Fixed-bed Reactormentioning
confidence: 99%
See 1 more Smart Citation